A method to increase the workability retention of concrete with limestone calcined clay based cementitious system using a dispersing agent containing sodium hexametaphosphate. (September 2022) - Bhattacherjee, Shantanu; Jain, Smrati; Santhanam, Manu
Abstract: This study is focused on increasing the workability retention of concrete with high replacements of cement by limestone calcined clay, or LC2 (≥45% by weight of binder). The effect of three commercially available PCE-based superplasticizers (SPs) on workability retention is studied. To enhance the retention ability of the concrete with SPs, a combination of sodium hexametaphosphate and anhydrous sodium carbonate as a dispersing agent (DA) is used. The study is conducted in three phases. In phase 1, the effect of DA with different SPs is studied on a concrete and concrete equivalent mortar with LC2 content of 45%. Flow table test and slump cone test are performed on mortar and concrete to assess the workability retention for 2 h from adding water to the mix. Additionally, the cube compressive strength is measured at 3, 7, and 28 days from casting. The addition of DA increases the workability retention of the concrete significantly. A slump of more than 200 mm is achieved after 2 h for concrete with DA against less than 100 mm without DA. Further, in phase 2, the effect of change in LC2 content on workability retention and compressive strength is studied. The LC2 contents used in this phase are 25, 35, 55, and 75%. It is observed that with an increase in the LC2 content, the workability retention drastically reduces for mortar mixes with only SPs. However, the addition of DA increased the workability retention of the mixes. The slump increased from 5 mm to 205 mm for a concrete mix with 75% LC2 content with addition of 0.5% DA. The last phase of the study is focused on evaluating the effect of SP and DA on the hydration kinetics of the mix by isothermal calorimetry. The combination of SP and DA acts as a strong retarder, resulting in a lower compressive strength at 3 days from casting. However, a minor reduction in compressive strength is seen at later ages with the addition of the DA. Further, a theoretical model is proposed elaborating the interaction of DA with the binder system, resulting in increased workability retention.